"Keeping the family side ticking along". Issue 2 (8th June 2015) - Margaret Shaffer and Dr Mina Westman, Professor; Baker, Charlotte; Ciuk, Sylwia
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to explore the work-family interface of two non-traditional forms of expatriation. The paper contributes to existing research by comparing and contrasting the experiences of international business travellers and rotational assignees, pointing out the similarities in their experiences but also showing considerable differences in how the work-family interface plays out in these two groups. Design/methodology/approach – In line with the exploratory nature of the research, the authors carried out a qualitative case study drawing on interview data with rotators and international business travellers (n=20). In order to get more in-depth insights into the experiences of these two groups of assignees, the authors also used the photo-elicitation technique, which corresponds with the recent recognition that the evolving nature of international assignments requires alternative methods of inquiry to enhance the understanding of the challenges faced by them. Findings – The study points to four major factors affecting the work-family interface: time spent away, unpredictability of work schedules, limited ability to exercise control over it as well as limited availability of organisational support. The findings illustrate that while these factors impact international business travellers and rotators alike, their intensity varies considerably in the experiences of these two groups. Research limitations/implications – The research is based on a single case study and a small sample which needs to be considered when discussing the implications of the findings. Future research can valuably extend and build on the here reported observations. Practical implications – A number of practical implications are discussed, notably pertaining to the ways in which organisations can mitigate the challenges encountered by international business travellers and rotators. Originality/value – The papers focuses on two groups of assignees that are underrepresented in the expatriate literature despite their increasing empirical significance in international business.